«Умный в гору не пойдет пойдет…» : использование электронных корпусов для диахронных исследований - GYÖRFI, BEÁTA (SlavVaria, 2021)
“Work smart, not hard”: the use of electronic corpora for diachronic research. The present article is meant to be an experiment. Through the study of a specific linguistic problem – the use of discourse enclitics in two registers of the Old Russian langu age – the advantages and disadvantages of the use of electronic corpora in similar investigations is demonstrated in the research research.